Pengaruh Kompensasi Dan Budaya Organisasi Terhadap Kinerja Pegawai Dengan Motivasi Kerja Sebagai Variabel Perantara - Ahmad Shalahuddin; Berman Paulus Marpaung (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2014)
Remuneration policy for employees of the Directorate General of Taxation is based on the idea of the need for organizations to pay attention to the interests of its employees who have a wide range of needs. Changes made to the Directorate General of Taxation has given satisfactory results of the shareholders. However, the bureaucratic reform journey tarnished the behavior of some unscrupulous employees DGT suspected of committing criminal offenses still be receiving gratification and misuse of authority. It shows that the remuneration policy has not been able to change the nature of the tax officials and necessary need to be assessed on matters that may significantly affect the performance of employees. The aims of this research are to analyze the influence of compensation and organizational culture, and its impact toward work motivation and employee’s performance at Kantor Pelayanan Pajak Pratama Pontianak. Compensation and organizational culture are independent variables, performance of employee as dependent variable, with motivation as an intervening variable. The sample for this research is all employees at this organization (102 persons). The software that used to analyze the data is statistical software SPSS 17. The researcher has used normality test, linearity test, heteroskedasticity test, and path analysis. As the results, the coefficient rate of direct influence of organizational culture toward employee performance is bigger than indirect influence of organizational culture toward employee performance through work motivation. So as to improve employee performance is more effectively through increasing the organizational culture.